Parameningeal embryonic rhabdomyosarcoma in adult - Huamán Muñante, Jose (2019)
A 22-year-old female patient, with 2-month disease time, presented with epiphora, mild conjunctival erythema and pruritus in the right eye. A small greenish-colored tumor appeared at the level of the internal canthus associated with mild bipalpebral edema. The edema progresses limiting the vision in said eye, associating the protrusion of the right eyeball. An anatomopathological study of the nasosinusal tumor was performed, presenting hyperchromatic cellular nests with an infiltrative aspect and the immunohistochemical study concluded as embryonic rhabdomyosarcoma. Chemotherapy was performed.